Consumption of Free Sugar Predicts Nutrient Intake of Saudi Children - Mumena, Walaa Abdullah (Frontiers in Nutrition, 2021)
Data concerning the association between free sugar intake and nutrient intake in children in the Middle East are not available. This study aimed to explore the association between the consumption of free sugar and nutrient intake among Saudi children. A cross-sectional study included 424 Saudi children ages between 6-12 years old and their mothers. An online survey collected sociodemographic data from mothers. Trained data collector personal contacted mothers to arrange for a phone interview in order to collect 24-hour dietary recall to assess the dietary intake of children. Only 0.90% of children consumed free sugar within the recent recommendation of the World Health Organization (WHO) of < 5% of total energy intake, whereas 10.6% of children consumed free sugar < 10% of total energy intake. The percentage of free sugar intake was associated negatively with total energy intake. Multiple linear regression analysis of free sugar consumption and nutrient intake adjusting for children’s age and sex indicated that a higher percentage of free sugar intake significantly predicted lower intake of saturated fat, fiber, sodium, potassium, calcium, iron, zinc, and vitamin B12. Excessive intake of free sugar predicted a lower intake of essential nutrients. Interventions that aim to reduce the intake of free sugar are urgently needed in order to improve the diet of growing children. Future research to explore top food sources of free sugar is needed to establish effective interventions that aim to limit free sugar intake among children.